PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA GURU SMP NEGERI SE-KECAMATAN CIASEM KABUPATEN SUBANG - Pratiwi Lesmanawati (Universitas Buana Perjuangan Karawang, 2018)
ABSTRACT The research was conducted in Ciasem Subdistrict Subang District West Java on all SMP Negeri which were in Ciasem Subditrict i.e : SMPN I, SMPN 2, SMPN 3 and SMPN 4. The aim of this research was to analysis of Management, Organization Culture and Motivation on the Teacher job description of SMP Negeri in Ciasem Subdistrict, Subang District West Java. The result showed that the leader of Management, Organization culture, Motivation and Teacher Job description were well. The individual correlation refered that the correlation of Management and Organization Culture gave of correlation coefficient value (r) of 0.603 and they refered strong correlation to direction and positive. It mean the increase of Management would increase Organization Culture. It in stead of that. The correlation of Organization Culture and Motivation gave correlation coefficient value (r) of 0,632 and they refered strong correlation to direction and positive. It mean the increase of Organization culture would increase Motivation. It in stead that. The correlation of Management and Motivation gave correlation coefficient value (r) of 0.514 and they refered strong correlation to direction and positive. It mean the increase of Management would increase Motivation. It in stead that. In this research gave influence Management, Organization culture and Motivation on Teacher job description of 23,4 %, 24,5 % and 27,4 % respectively. They refered that the influence of Motivation on Teacher Job description was higher in contribution than Managemet and Organization Culture. In simultaneous correlation of Management, Organization Culture, and Motivation were significance influence on Teacher job description. They gave R Square of 75,3%, They refered Teacher job description was influenced by Mangement, Orgnanization Culture and Motivation. While remainder of 24.7 % were influenced by other variables which no test in this research. Key words : management, organization culture, motivation.